Large accumulations of maize streak virus in the filter chamber and midgut cells of the leafhopper vector Cicadulina mbila - Ammar, El-Desouky; Gargani, Daniel; Lett, Jean M; Peterschmitt, Michel (Archives of virology, 2009)
Maize streak virus (MSV, Mastrevirus, Geminiviridae) is persistently transmitted by Cicadulina mbila, apparently without propagation in its leafhopper vector. MSV was shown earlier by quantitative PCR to accumulate in the alimentary canal of C. mbila. We examined the alimentary canals of C. mbila leafhoppers that acquired MSV from diseased plants for various acquisition access periods (AAP) by immunofluorescence confocal laser scanning microscopy (iCLSM) and by immunogold labelling transmission electron microscopy (iTEM). Following a 7-day AAP and a 7-day inoculation period (IP) on healthy seedlings, MSV was detected by iCLSM mainly in the filter chamber and anterior midgut. Using iTEM, large accumulations of MSV particles, usually enclosed in membranous vesicles, were detected only in cells of the midgut, inside and outside the filter chamber, following 14- or 30-day AAPs, and also following 7-day AAP and 7-day IP on healthy plants. No virus was detected in the control non-vector species C. chinaï. Coated pits or vesicles, typical of clathrin-mediated endocytosis, were not observed. We discuss an alternative endocytosis pathway and suggest that the MSV accumulations are stored in endosomes in the midgut epithelial cells.